Determinants of Demand For Money and The Velocity of Money in Indonesia - Prasetyo, Alvin Sugeng (Journal of Developing Economies, 2018)
The demand for money is one of many monetary economics topics that is popular in every country. This study aims to test and analyze some influential factors of the demand for money and the velocity of money in Indonesia. The data source of this study takes from the International Financial Statistics. The method used is ARDL with a period of 2000Q1-2017Q4. The result of the analysis shows that all the variables are stationary on the I (0), a Bound test shows there are cointegration and the selected model that is ARDL (4, 2, 0, 0, 0). The study concludes that the economic growth and the growth rate of the rupiah/USD give a significant effect toward the growth of M2 in the long term and short term, and the velocity of money in Indonesia has an increased trend. Keywords: M2, ARDL, economic growth, the growth rate of the rupiah/USD JEL Classification: O49